2023
DOI: 10.1002/smll.202300756
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Pt Particles onto Mesoporousized ZnO Holey Cubes for Triethylamine Detection with Multifaceted Superiorities

Abstract: Designing sensing materials with integrating unique spatial structures, functional units, and surface activity is vital to achieve high‐performance gas sensor toward triethylamine (TEA) detection. Herein, a simple spontaneous dissolution is used with subsequent thermal decomposition strategy to fabricate mesoporousized ZnO holey cubes. The squaric acid is crucial to coordinate Zn2+ to form a cubic shape (ZnO‐0) and then tailor the inner part to open a holey cube with simultaneously mesoporousizing the left cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Nitrogen adsorption/desorption tests (Figure S3) showed that the BET-specific surface areas of In 2 O 3 and MZO samples were 57.24, 62.52, 62.78, and 59.81 m 2 /g (Table ), indicating mesoporous materials with an average pore size of 16–18 nm . Moderate Co 3 O 4 decoration significantly increased the specific surface area of the material, while excessive Co 3 O 4 tended to aggregate on the surface of the main material In 2 O 3 , reducing the effective contact area and specific surface area . Generally, the hollow framework structure, large specific surface area, high porosity, and small grain size provide abundant pathways for gas transport, facilitating gas adsorption–desorption and interface charge transfer during gas sensing processes …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nitrogen adsorption/desorption tests (Figure S3) showed that the BET-specific surface areas of In 2 O 3 and MZO samples were 57.24, 62.52, 62.78, and 59.81 m 2 /g (Table ), indicating mesoporous materials with an average pore size of 16–18 nm . Moderate Co 3 O 4 decoration significantly increased the specific surface area of the material, while excessive Co 3 O 4 tended to aggregate on the surface of the main material In 2 O 3 , reducing the effective contact area and specific surface area . Generally, the hollow framework structure, large specific surface area, high porosity, and small grain size provide abundant pathways for gas transport, facilitating gas adsorption–desorption and interface charge transfer during gas sensing processes …”
Section: Resultsmentioning
confidence: 99%
“…41 Moderate Co 3 O 4 decoration significantly increased the specific surface area of the material, while excessive Co 3 O 4 tended to aggregate on the surface of the main material In 2 O 3 , reducing the effective contact area and specific surface area. 2 Generally, the hollow framework structure, large specific surface area, high porosity, and small grain size provide abundant pathways for gas transport, facilitating gas adsorption−desorption and interface charge transfer during gas sensing processes. 42 Further analysis of the crystal structure and lattice parameters of the sensing material was conducted by using X-ray diffraction (XRD).…”
Section: Synthesis Methods and Structural Characterization Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following our previous procedures [29,30], the gas sensors were fabricated. At the very beginning, a homogeneous paste was formed by mixing 0.1 gas-synthesized powder with 0.2 mL deionized water.…”
Section: Fabrication and Testing Of Gas Sensormentioning
confidence: 99%